One-pot synthesis of 2-arylated and 2-alkylated benzoxazoles and benzimidazoles based on triphenylbismuth dichloride-promoted desulfurization of thioamides - Koyanagi, Arisu; Murata, Yuki; Hayakawa, Shiori; Matsumura, Mio; Yasuike, Shuji (Beilstein Journal of Organic Chemistry, 2022)
The development of novel and efficient synthesis methods for 2-substituted benzazole derivatives is of interest as they are biologically active substances. Herein, a simple method for the synthesis of 2-aryl- and 2-alkyl-substituted benzazoles is described. The reaction of 2-aminophenols with thioamides at 60 °C in the presence of triphenylbismuth dichloride in 1,2-dichloroethane as a promoter afforded various 2-aryl- and 2-alkylbenzoxazoles in moderate to excellent yields under mild reaction conditions. This method could also be applied to the synthesis of benzimidazoles and benzothiazoles. This study presents the first use of triphenylbismuth dichloride to produce benzimidoyl chloride from thioamides by desulfurization and chlorination, as well as its application to the synthesis of 2-substituted benzazoles.
Keywords: benzazole; bismuth; cyclization; desulfurization; thioamide